A prospective diet-wide association study for risk of colorectal cancer in EPIC - Papadimitriou, N; Bouras, E; van den Brandt, PA; Muller, DC; Papadopoulou, A; Heath, AK; Critselis, E; Gunter, MJ; Vineis, P; Ferrari, P; Weiderpass, E; Boeing, H; et al. (Elsevier, 2021)
Background & Aims: Evidence regarding the association of dietary exposures with colorectal cancer (CRC) risk is not consistent with a few exceptions. Therefore, we conducted a diet-wide association study (DWAS) in the European Prospective Investigation into Cancer and Nutrition (EPIC) to evaluate the associations between several dietary exposures with CRC risk.